Patient Blood Management. Three pillar strategy to improve outcome through avoidance of allogeneic blood products - Gombotz, Hans; Hofmann, Axel (Springer, 2013)
Blood transfusions are commonly viewed as life-saving interventions; however, current evidence shows that blood transfusions are associated with a significant increase of morbidity and mortality in a dose-dependent relationship. Not only explanatory models of basic research but also the results from randomized controlled trials suggest a causal relationship between blood transfusion and adverse outcome. Therefore, it can be claimed that the current state of science debunks the long held belief in the so-called life-saving blood transfusion by exposing the potential for promoting disease and death. Adherence to the precautionary principle and also the fact that blood transfusions are more costly than previously assumed require novel approaches in the treatment of anemia and bleeding. Patient Blood Management (PBM) allows transfusion rates to be dramatically reduced through correcting anemia by stimulating erythropoiesis, minimization of perioperative blood loss and harnessing and optimizing the physiological tolerance of anemia. A resolution of the World Health Assembly has endorsed PBM and therefore morbidity and mortality should be significantly reduced by lowering of the currently high blood utilization rate of allogeneic blood products in Austria, Germany and Switzerland.